Assessment of serum uric acid level among patients with rheumatoid arthritis - Roble, Hassan Y.; Sultana, Rosy; Moniruzzaman, Mohammad; Hassan, M. Zahid (International Journal Of Community Medicine And Public Health, 2022)
Background: Rheumatoid arthritis (RA) is a long-term autoimmune disorder that primarily effects elderly population and commonly involves pain in the joints (the wrist and hands). Gout is a form of arthritis caused by excess uric acid in the blood stream, which can affect several joints. The co-occurrence of RA and gout in the same patient is rarely reported. The aim of this study was to assess the level of serum uric acid among patients with RA, and to observe any associations of serum uric acid levels with RA. Methods: In a descriptive cross-sectional study, a total of 70 blood samples were collected from patients. Anti-cyclic citrullinated peptide (anti-CCP) antibodies measured by ELISA method, serum C-reactive protein (CRP), Rheumatoid factor (RF) measured by latex agglutination test and serum uric acid levels measured with semi-autoanalyzer were carried out. Data was analyzed using a statistical package for social science for windows version 15.0. A p<0.05 was taken as level of significance. Results: Out of a total of 70 subjects, 15 (21.4%) were positive for RF, anti-CCP antibodies positivity was present in 10 (14.3%) of the cases and serum high sensitive CRP was present in 36 (51.43%) of the cases. Of 70 cases. The 50 had hyperuricemia (23 male vs 27 female). Distribution of subjects having a high serum uric acid level on the basis of RF, anti-CCP Ab, and CRP status were statistically different. Conclusions: The present study summarizes the level of uric acid in patients with RA (either seropositive or seronegative arthritis). The data concluded that serum uric acid did not show association with RA as revealed by the lack of association with specific markers.